Reflection and Virtual Reality: From the Etymological Analysis of Concepts to the Understanding of Essential Relationships - Anikina V.G (Moscow State University of Psychology and Education, 2021)
The study of virtual reality in psychology and pedagogy requires an understanding of the essential connections and relationships of VR with various mental phenomena, and above all - reflection.The urgency of considering this problem is due to the search of VR developers and those who use virtual technologies in practice, including VR didactics, practical psychology, for a solution to the issue of self-management of systems with VR.Can VR exercise the reflective function of the mind represented in the processes of self-development, self-determination, self-management of the individual? The first step in solving this issue is to identify and describe the essential relations of reflection and virtual reality.For this, an etymological analysis of the concepts of reflection and virtual reality was carried out.The paper highlights the intersections in the semantic meanings of these concepts.Our analysis allowed us to employ the functional model of reflection (Anikina V.G.), within which VR can be considered as a 'chronotope' of reflection - the space-time continuum of the presence of Self 'outside' the situation, in relation to which the reflective process is meaningfully carried out.The paper outlines the possible ways of using VR in the development and formation of reflection and universal reflective actions in the educational process.